Content-Based Instruction In Communicative Language Teaching - Zamani Roodsari, Sedighe; Harrison, Jamie (English Lecturers and Teachers Association (ELTA), 2024)
Content-based instruction (CBI), in which the teaching is organized around the content (Brinton et al., 1989), exposes students to different aspects of a new language while learning content. CBI models and paradigms have had major contributions to language and content learning and are known as holistic approaches to foreign language education (Sariani et al., 2022; Stryker & Leaver, 1997). Although the pillars of Content-Based Instruction are deeply rooted in the principles of communicative language teaching, they apply form-focused instruction (FFI) in teaching certain features in the target language (Elgün-Gündüz, Akcan & Bayyurt, 2012). The current study investigates a language learning experience in adult education through some of the distinctive characteristics of CBI including teaching content through language criteria, integrating language skills, involving students actively in all phases of the learning process, choosing content relevant to students’ lives, interests, academic goals, and selecting authentic texts and tasks reflecting the cultural values of the target language (Bula Villalobos, 2014). The participants of this study are prospective language teachers who are exposed to a foreign language in a graduate Applied Linguistics in Second Language Acquisition course. By utilizing foreign language instruction within the linguistics course, students experience the key elements of language (phonetics, phonology, morphology, syntax, pragmatics, semantics, orthography) through an active learning environment, enhancing students’ learning of linguistic features while also engaging them in the language-learning process. This study shares the structure and outline of the embedded language experience as it relates to the linguistic content of the course and engages participants in a discussion about possibilities and next steps to consider in teaching content in a foreign or second language. Data collection includes observations, reflective journals, and assignment artifacts. Data are analyzed using a grounded theory approach to understand the experiences of the participants in this course. Results of the study suggest that through language instruction (Parsi), the researchers aim to add a layer of discussion to a new chapter of CBI paradigms. Keywords: Content-Based Instruction; Language Instruction; Language Teaching